COMPARISON OF MEAN PAIN SCORE OF THE LOCALLY INJECTABLE CORTICOSTEROID AND COMBINATION OF ORAL AND TOPICAL NONSTEROIDAL ANTI-INFLAMMATORY AGENTS FOR THE TREATMENT OF TENNIS ELBOW” - Afzal Javid; Muhammad Nadeem Yousaf; Muhammad Javaid Iqbal (Journal of University Medical & Dental College, 2017)
ABSTRACT INTRODUCTION: Tennis elbow is a condition characterized by pain and tenderness over the lateral epicondyle of the humerus and pain on resisted dorsiflexion of the wrist, middle finger or both.1 Tennis elbow is a common musculoskeletal condition affecting 1% to 3% of the adult population.2 It is a common condition that usually affects patients between 30 and 50 years of age. So far, there are numerous treatment options available to control the symptoms of this condition, like the use of NSAID’s drugs, injectable corticosteroids, exercises, and physiotherapy etc . However, none of these provide satisfactory results.5 Results of this study will help to adopt the most appropriate treatment option for the patients with tennis elbow to reduce their symptoms and morbidity. Objectives: To compare mean pain score of locally injectable steroid and the combination of oral and topical non-steroidal anti-inflammatory agents for the treatment of tennis elbow. MATERIALS & METHOD Study Design: Randomized control trials Setting: The study was conducted at Orthopedic Departments Punjab Medical College and Affiliated Hospitals Faisalabad. Duration of Study: 05-01-2014 to 04-07-2014 (Six months) Results: Out of 60 cases 38 (63.3%) were males and 22 (36.7%) were females. Mean age was 43.07±7.40 years. Mean VAS in group A after 6 weeks of treatment was 5.87±1.008 and in group B it was 0.83±0.648 (p= 0.0001). Conclusion: This study shows that the locally injectable corticosteroids are an excellent method for relieving symptoms in patients with tennis elbow as opposed to a combination of topical and oral NSAID’s.